Analisis Tingkat Pengetahuan, Sikap, dan Kesadaran Peserta Didik terhadap Pengelolaan Sampah di SMA Negeri 6 Skouw: Penelitian - Midah Nurhidayah; Ardian Hangga Kelana; Sittin Masawoy; Febri Listianingrum; Pusmiati; Taufik Mubarak; Sakka Irawan; Titia Erika Sarlota Awom (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the level of knowledge, attitudes, and awareness of students towards waste management at SMA Negeri 6 Skouw. A descriptive quantitative approach was used in this study with a survey method through a closed area distribution. The research instrument was a questionnaire consisting of 3 main aspects: knowledge, attitudes, and awareness of students towards waste management. The research sample consisted of 48 respondents selected by purposive sampling. The results showed that students had a very positive profile in the three main aspects of waste management. In the knowledge aspect, students were in the capable category as evidenced by their high understanding of the classification of organic and inorganic waste and their risk impacts. This good knowledge was then embedded linearly with students' attitudes which were classified as positive so that a sense of personal responsibility arose to maintain the cleanliness of the school environment. Furthermore, this was reflected in the high level of awareness and demonstrated the readiness and commitment of the trained participants in carrying out real waste management efforts.